(3EQTGO GdeHJOi hJPcQI GdefJgis - (3eMeO Hf GdMSjf Hf oHfOGQ, CHh GdYR GdbdGfSj GdhGSWj ,J (B521 (3g` s
(3ChdgG (B:s
(3SCdJ habc Gddg hEjGi GdYed HWGYJg Cf Cedi Ydjc cJGHkG jTJed Ydi bQGAGJ GdYTQI CFeI GdGeUGQ hGdMLGR hGdTGe hGdYQGb s
(3BNQgG (B:s
(3BNQg fGbU jfJgi HGKfGA GdbQGAGJ ai ShQI GdGYdi s
(3GdejcQhajde Hg Jda HSjWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B101 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B236s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B66s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs